Role of Public Relations Dinas Pariwisata dan Kebudayaan Ambon City to Educate People with Intercultural Communication Approach - Ruby Marsal Parera (PAX HUMANA, 2018)
Ambon is a region with the riches natural resources that which potential and has own characteristics. Dinas Pariwisata dan Kebudayaan Ambon city as an instance that has important role in the progress of tourism need Public Relations to educate the people related from tourism with utilize communication media. Education doing with approach from intercultural communication so the delivery process of the message and the information can be effective, remember about the background of people culture that diverse. The purpose of this research is the roles of Public Relations can configurate people related from tourism so that local and non local people interested to visit Ambon city. The method of this research is qualitative descriptive. The research results is some of the role of public relations in Dinas Pariwisata dan Kebudayaan Ambon city had been done, however is not optimal because lack of human resources. In addition, Dinas Pariwisata dan Kebudayaan Ambon city just promotes tourism without educating people so that people do not understand about tourism. Education using the intercultural communication approach had been done on interpersonal communication but not for mass communication.